MATH SOLVE

5 months ago

Q:
# What are the solutions of the equation f (x) = g(x)?

Accepted Solution

A:

Answer:

1 and 3

Explanation:

We are given that:

f(x) = 2ˣ - 2

g(x) = 3x - 3

We want to get the solution of f(x) = g(x). This means that we want to get the values of x that make the two solutions equal

Since the choices givens all belong to the given table, we can simply get the solution by examining the table and comparing f(x) with g(x) at each value:

At x = -1:

f(x) = -3/2

g(x) = -6

f(-1) is not equal to g(-1)

Therefore, this is not a solution

At x = 0:

f(x) = -1

g(x) = -3

f(0) is not equal to g(0)

Therefore, this is not a solution

At x = 1:

f(x) = 0

g(x) = 0

f(1) is equal to g(1)

Therefore, this is a solution

At x = 2:

f(x) = 2

g(x) = 3

f(2) is not equal to g(2)

Therefore, this is not a solution

At x = 3:

f(x) = 6

g(x) = 6

f(3) is not equal to g(3)

Therefore, this is a solution

At x = 4:

f(x) = 14

g(x) = 9

f(4) is not equal to g(4)

Therefore, this is not a solution

At x = 5:

f(x) = 30

g(x) = 12

f(5) is not equal to g(5)

Therefore, this is not a solution

Based on the above, the only solutions among the given choices are 1 and 3

Hope this helps :)

1 and 3

Explanation:

We are given that:

f(x) = 2ˣ - 2

g(x) = 3x - 3

We want to get the solution of f(x) = g(x). This means that we want to get the values of x that make the two solutions equal

Since the choices givens all belong to the given table, we can simply get the solution by examining the table and comparing f(x) with g(x) at each value:

At x = -1:

f(x) = -3/2

g(x) = -6

f(-1) is not equal to g(-1)

Therefore, this is not a solution

At x = 0:

f(x) = -1

g(x) = -3

f(0) is not equal to g(0)

Therefore, this is not a solution

At x = 1:

f(x) = 0

g(x) = 0

f(1) is equal to g(1)

Therefore, this is a solution

At x = 2:

f(x) = 2

g(x) = 3

f(2) is not equal to g(2)

Therefore, this is not a solution

At x = 3:

f(x) = 6

g(x) = 6

f(3) is not equal to g(3)

Therefore, this is a solution

At x = 4:

f(x) = 14

g(x) = 9

f(4) is not equal to g(4)

Therefore, this is not a solution

At x = 5:

f(x) = 30

g(x) = 12

f(5) is not equal to g(5)

Therefore, this is not a solution

Based on the above, the only solutions among the given choices are 1 and 3

Hope this helps :)